A Nominally New Dictionary of Ancient Greek: GI, GE, GD and LSJ9 - S. Douglas Olson (Emerita)
This article is a close examination of portions of Franco Montanari's new series of Greek dictionaries (GI, GE and GD), with particular attention to a number of lemmata beginning with alpha and mu in the recent German-language edition. A general consideration of lexicographic best practices is offered in that light. Contrasts are drawn throughout between LSJ9 and Montanari in regard to the handling and checking of primary references, the choice of lemmata and the organization of entries, and the relationship between the two works is traced via study of a group of individual lemmata beginning with alpha. The article concludes with a detailed analysis of the handling of ἀλαός, ἀλαόω and μάκελλον and cognates in LSJ9 and Montanari, with alternative suggestions for how the material might be most effectively organized, presented and understood.